Evaluation of sunflower (Helianthus annuus L.) germplasm lines for genetic diversity: Evaluation of sunflower (Helianthus annuus L.) germplasm lines for genetic diversity - E UMARANI; A SARITHA; AV RAMANJANEYULU (Journal of Oilseeds Research, 2023)
In the present investigation, estimation of the genetic diversity among thirty five germplasm lines of sunflower was undertaken by using Mahalanobis D2 analysis. Based on the relative magnitude of D2 values, the experimental material was distributed into six clusters. Out of six clusters, cluster I was the largest comprising of nineteen lines. Single plant yield, plant height, volume weight together contributed maximum (82.85 %) to the total genetic divergence. Maximum inter cluster distance was exhibited between clusters II and IV. The greater the distance between two clusters, the wider the genetic diversity among the genotypes of these clusters. Hence, hybridization between the genotypes from these clusters would produce high heterotic recombinants.